Analysis of the Effectiveness of Bank Merger Profitability - Anom Fajar Puji Asmoro; Noor Syaifudin; Ramdany Ramdany (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The purpose of this study is to analyze post-merger profitability, company value growth throughsustainable growth rateand supporting factors for mergers, financial feasibility pre-merger and acculturation of work culture at Bank Syariah Indonesia. The population in this study was quarterly financial reports.legacy(BNIS, BRIS, and BSM) for the period 2017 - 2020 and BSI quarterly financial reports for the period 2021 - 2024 and in-depth interviews with 3 BSI employees with different legacy backgrounds. The method used is the approachmixed methodswith typeconvergent parallel design. The quantitative results obtained show significant differences in ROA, ROE, NPM and SGR before and after the merger. While qualitatively, the financial feasibility analysis of legacy banks shows that all three legacies are in the healthy bank category, while the interview results related to work culture show the integration of legacy culture, similarity of vision and mission and merging into BSIone culture.